The Bosnian-Croatian-Serbian Adnominal Possessive Dative at the Syntax-Pragmatics Interface - Pennington, James Joshua (Slavia Centralis, 2020)
In Bosnian, Croatian, and Serbian, the adnominal possessive dative (APD) construction is used alongside the nominal adjectival construction to express possession. APD usage is double-edged – i.e., there are both issues of sociolinguistics/perceptual dialectology involved as well as more formal syntacticpragmatic ones. My respondents consistently labeled APD usage as "archaic," "old-fashioned," "characteristic of the uneducated," or "country-talk". However, judging by very similar acceptance levels of APDs in particular contexts in all dialects, it appears that semantic role of the possessor and the level of contextual effects and processing load involved in interpreting possessive constructions weigh heavily on their acceptance. Therefore, I offer a model that attempts to capture APD usage in terms of a set of hierarchical relationships between the "possessor" and the "possessed".
Keywords: Adnominal possessive dative (dative of interest/sympathy); Bosnian-Croatian-Serbian; syntax-pragmatics interface; perceptual dialectology; dialect geography